Antibacterial Efficacy of Biosynthetic Zinc Oxide Nanoparticles by Lactobacillus Plantarum Combined with Poly-?-hydroxybutyrate Against Pathogenic Bacteria (Indian Journal of Forensic Medicine & Toxicology, 2020)
The good capability of zinc-tolerant probiotic of Lactobacillus plantarum tolerating high concentrationsof Zinc+2 and producing Zinc Oxide Nanoparticles highlights the unique characteristics of thesebacteria as a natural microbial cell nano-factory for a more efficient and environmentally friendlyprocess of biosynthesis of these nanoparticles. The morphological and structural properties of Zinc OxideNanoparticles were determined by X-ray diffraction, Atomic Force Microscope and Field Emission ScanningElectron Microscope showed that the synthesized nanoparticles were crystalline, moderately stable, roughlyspherical, hexonal in shape and pureWe examined the antibacterial activity of the Zinc Oxide Nanoparticles and Zinc Oxide Nanoparticles/Poly-?- hydroxybutyrate bionanocomposite on some pathogenic bacteria .It is clear in this the study thatZinc Oxide Nanoparticles/Poly-?-hydroxybutyrate bionanocomposite has stronger inhibitory effect onpathogenic bacteria compared with Zinc Oxide Nanoparticles only because the bionanocomposites exhibitedreduced water uptake and superior gas as well as vapour barrier properties and causes increasing damage ofthe pathogenic bacteria.